Motivation and the academic – where the drivers sit. Issue 6 (11th July 2016) - Johnston, Alan
Abstract : Purpose: – The purpose of this paper is to investigate the key drivers for motivation within a small team of academics within a relatively small UK university. Design/methodology/approach: – The research follows a combined interpretivist and ethnographic stance and using a mixed methods approach. Findings: – The research identifies that fundamentally academics are driven by the desire for expertise and a search for meaning, while material reward and a need for power play a low significance in their forces. Also increase in managerialism has led to reductions in motivation. Research limitations/implications: – The paper provides a limited focus due to the nature of being a small scale study. Practical implications: – The paper considers the drivers which motivate academics. Managers and HR departments may consider approaches to managing and leading individuals to achieve improved organisational performance. Originality/value: – The paper focuses on motivational drivers within the academy.